1996
DOI: 10.1080/07448481.1996.9936854
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of African American Collegiate Adult Children of Alcoholics

Abstract: The authors examined the relationship between students at a Black university who were adult children of alcoholics (ACOAs) and students who were not children of alcoholics (non-ACOAs) regarding levels of self-esteem, health in the family of origin, and social support during adolescence. The study participants were African American undergraduate students who responded to five surveys. The only significant relationship found was with results from the Michigan Alcoholism Screening Test (MAST). Level of drinking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Perkins and Berkowitz (1991) and Pullen (1994) also reported increased rates of alcohol-related problems for COAs compared with non-COAs. Rodney and Rodney (1996) found that black male COAs reported greater drinking than black non-COAs.…”
Section: Family History and Parents' Behaviormentioning
confidence: 92%
“…Perkins and Berkowitz (1991) and Pullen (1994) also reported increased rates of alcohol-related problems for COAs compared with non-COAs. Rodney and Rodney (1996) found that black male COAs reported greater drinking than black non-COAs.…”
Section: Family History and Parents' Behaviormentioning
confidence: 92%
“…Furthermore, differences between family history positive and negative individuals in rates of alcohol problems (Sher et al, 1991) and diagnosable alcohol use disorders (Knight et al, 2002;Pullen, 1994;Sher et al, 1991) have been observed. Knight et al (2002) found that those who reported being the child of a problem drinker were more likely to be diagnosed with alcohol dependence (but not alcohol abuse), and Rodney and Rodney (1996) found greater drinking for African American male children of alcoholics (COAs) than nonCOAs. In general it appears that those studies that find more problematic alcoholic involvement among college students with a family history of alcoholism have employed more conservative definitions of family history (see Baer, 2002), problem-based (as opposed to consumption-based) measures, and better designs from the perspective of sampling strategy and sample size.…”
Section: Sexmentioning
confidence: 99%
“…For instance, self-esteem has been negatively correlated with smoking frequency (Botvin et al, 1993), suppressed anger (Johnson & Greene, 1991), drug abuse (Unger, Kipke, Simon, Montgomery, & Johnson, 1997), and depression symptomatology (Caldwell, Antonucci, Jackson, Wolford, & Osofsky, 1997) in African American children and adolescents. Another recent study found that drinking level was negatively related to self-esteem in African American college students who had alcoholic parents (Rodney & Rodney, 1996). Thus, self-esteem is an important index of African American adolescents' well-being.…”
Section: Self-esteemmentioning
confidence: 99%